An efficient Fourier ptychographic microscopy method based on optimized pattern of LED angle illumination. (November 2020) - Mao, Haifeng; Wu, Xiaohui; Zhao, Jufeng; Cui, Guangmang; Hu, Jinxing
Highlights: Propose an efficient method based on optimized pattern of LED angle illumination. Obtain the theoretical expandable spectrum range and the spectrum distribution in Fourier space of all LEDs. Use image quality assessment to extract differential expression between an arbitrary LED and full LEDs illumination. Combine the redundancy of picture information to arrive at a new LED illumination strategy. Abstract: Considering angle diversity and synthetic aperture, Fourier ptychographic microscopy (FPM) could address contradiction of high resolution and wide field of view. However, in the conventional FPM method, large capture quantity leads to poor efficiency. So, an efficient FPM method based on optimized pattern of LED angle illumination is proposed. Firstly, from position relationship between the LED, aperture and sample, we obtain the theoretical expandable spectrum range and the spectrum distribution in Fourier space of all LEDs. Secondly, we u se image quality assessment methods to extract differential expressions between an arbitrary LED illumination and full LEDs illumination. Thirdly, the optimized angle illumination strategy is achieved according to the analysis of different expressions. Based on this method, we design a rhombus-based illumination method for the LED array to accelerate the FPM efficiency. Finally, we validate the effectiveness and efficiency of our method with both simulated and real experiments. The results indicate that our method can effectively improve the efficiency for FPM without sacrificing image reconstruction quality.